2014
DOI: 10.1016/j.physletb.2014.06.008
|View full text |Cite
|
Sign up to set email alerts
|

X-ray line signal from decaying axino warm dark matter

Abstract: We consider axino warm dark matter in a supersymmetric axion model with R-parity violation. In this scenario, axino with the mass $m_\axino\simeq 7$ keV can decay into photon and neutrino resulting in the X-ray line signal at $3.5$ keV, which might be the origin of unidentified X-ray emissions from galaxy clusters and Andromeda galaxy detected by the XMM-Newton X-ray observatory.Comment: 8 pages, 2 figures, typos corrected, discussion and one more figure added, the final journal versio

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 65 publications
1
34
0
Order By: Relevance
“…Nevertheless, a large number of DM models have been proposed to explain this signal. The ideas that have been proposed include sterile neutrinos , axions [70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85], supersymmetry [86][87][88][89][90][91][92] and a number of other mechanisms . We now show that the 3.5 keV line, if confirmed, can be easily accommodated within the framework of the minimal model.…”
Section: The 35 Kev Linementioning
confidence: 99%
“…Nevertheless, a large number of DM models have been proposed to explain this signal. The ideas that have been proposed include sterile neutrinos , axions [70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85], supersymmetry [86][87][88][89][90][91][92] and a number of other mechanisms . We now show that the 3.5 keV line, if confirmed, can be easily accommodated within the framework of the minimal model.…”
Section: The 35 Kev Linementioning
confidence: 99%
“…Among the various theoretical scenarios attempting to explain it, RPV SUSY with an LSP decaying to photon and a neutrino is a possibility. In bilinear RPV it was found that a warm-darkmatter axino with a mass of mα 7 keV can have the proper lifetime and relic density to account for the observed X-ray emission line through its decayα → γν [63,64]. The axino parameter space consistent with the aforesaid X-ray line can be seen in Fig.…”
Section: Implications For Dark Mattermentioning
confidence: 87%
“…For example, when m n > 2m e , the n can decay into an electronpositron pair through mixing with the Higgs field. The decay width is given by 11) where α ηH is the mixing angle between η and H, and β e = (1 − 4m 2 e /m 2 n ) 1/2 . For m n = 10 MeV, α ηH = 10 −4 , the lifetime of n becomes about 0.04 sec.…”
Section: Jhep08(2015)023mentioning
confidence: 99%